THE INFLUENCE OF CONSUMER ETHNOCENTRISM, PERCEIVED QUALITY AND BRAND AWARENESS ON BUYING INTEREST IN HOKA-HOKA BENTO IN BENGKULU CITY WITH BRAND IMAGE AS AN INTERVENING VARIABLE. - ramadhan, FAJRIANSAH RAMADHAN; Puspita, Veny; Army, M.Noor; Sumartono, Eko (UNIB Press, 2025)
This study analyzes the influence of consumer ethnocentrism, perceived quality, and brand awareness on consumers’ purchase intention toward Hoka-Hoka Bento in Bengkulu City, with brand image as a mediating variable. Using a quantitative explanatory method, data were collected from 150 respondents through purposive sampling and analyzed with PLS-SEM. The results show that perceived quality and brand awareness significantly influence brand image, while consumer ethnocentrism and perceived quality directly affect purchase intention. Brand image mediates the effect of perceived quality on purchase intention but not consumer ethnocentrism or brand awareness. The findings suggest that improving product quality and strengthening brand image are key strategies to enhance consumer purchase intention. The novelty of this study lies in examining consumer behavior toward a Japanese-inspired fast-food brand in a second-tier city, while its originality lies in testing the mediating role of brand image within an emerging market context where cultural perceptions strongly shape purchasing decisions.